Γ-Tocotrienol reduces human airway smooth muscle cell proliferation and migration. (June 2015) - Harada, Tomoya; Yamasaki, Akira; Chikumi, Hiroki; Hashimoto, Kiyoshi; Okazaki, Ryota; Takata, Miki; Fukushima, Takehito; Watanabe, Masanari; Kurai, Jun; Halayko, Andrew J.; Shimizu, Eiji
Abstract: Aims: Vitamin E is an antioxidant that occurs in 8 different forms (α, β, γ, and δ tocopherol and tocotrienol). Clinical trials of tocopherol supplementation to assess the impact of antioxidant activity in asthma have yielded equivocal results. Tocotrienol exhibits greater antioxidant activity than tocopherol in several biological phenomena in vivo and in vitro . We tested the effect of tocotrienol on human airway smooth muscle (ASM) cell growth and migration, both of which mediate airway remodeling in asthma. Main methods: We measured platelet-derived growth factor-BB (PDGF-BB)–induced ASM cell proliferation and migration by colorimetric and Transwell migration assays in the presence and absence of γ-tocotrienol (an isoform of tocotrienol). Key findings: PDGF-BB–induced ASM cell proliferation and migration were inhibited by γ-tocotrienol. This effect was associated with inhibition of RhoA activation, but it had no effect on p42/p44 mitogen-activated protein kinase (MAPK) or Akt1 activation. We confirmed that pharmacological inhibition of Rho kinase activity was sufficient to inhibit PDGF-BB–induced ASM cell proliferation and migration. Significance: γ-Tocotrienol could impart therapeutic benefits for airway remodeling in asthma by inhibiting human ASM cell proliferation and migration.